Pendampingan Posko LazisNU dalam Mensukseskan Kebijakan Pemerintah di Era New Normal di Desa Tegowangi Kediri - Anang Faruki; Mustajib (LP3M IAIFA Kediri, 2020)
The Covid-19 pandemic has disturbed people, not only in Indonesia but in all corners of the world. Each country has its own policy in dealing with and anticipating the spread of Covid-19 in its territory. After 5 months of implementing PSBB (Large-Scale Social Restrictions), Indonesia is now implementing a New Normal policy in the face of the Covid-19 Pandemic. The New Normal era, identic with the implementation of health protocols in all places and in various activities. Low awareness of citizens in using health protocols is one of the challenges that should be solved together. This devotion-based research aims to increase awareness of residents, especially tegowangi villagers in using health protocols while on the move. This research uses the PAR (Participatoty Action Research) method where the researcher participates in every activity carried out during the research. The object of research in this research is the residents of Tegowangi Village. This research was conducted together with the ZIS Institute (Zakat, Infaq, and Alms) which also participated in social activities in the Tegowangi Village area, the institution is LAZISNU Tegowangi branch. Research begins with an analysis of the needs of citizens in the face of the New Normal Era, then designing activities, carrying out activities, and evaluating the results of transformation activities that have been carried out. As a result of this research, the awareness of Tegowangi villagers in using health protocols in every activity, especially activities outside the home.